Infectious Coryza (Snot) in Chicken in Indonesia - Kusumaningsih, Anni; Poernomo, Sri (Indonesian Animal Sciences Society, 2000)
Infectious coryza (snot) is an infectious disease of poultry, especially chicken, caused by Haemophilus paragallinarum (Hpg). The bacterium is small gram negative, non-motile, microaerophilic, and nicotinamide adenine dinucleotide (NAD) dependent. In Indonesia, 3 serotypes of Hpg, A, B and C have been isolated. The course of the disease is usually about 1-3 weeks. In poultry farms with vaccination program, the mortality rate is very low, about 0-5%, but morbidity rate can reach 30-40% with loss of egg production up to 10-50%. Disease control with vaccination using a bivalent (A and C serotypes) or trivalent (A, B and C serotypes) killed vaccine is practiced. The treatments are carried out with drugs including antibiotics and sulpha preparation. Result of antibiotic sensitivity test of Hpg isolates shown that mostly of these isolates were resistance to colistin and streptomycin. Â Key words : Infectious coryza, Haemophilus paragallinarum, chicken